The bigger the better? Evidence of the effect of government size on life satisfaction around the world - Christian Bjørnskov; Axel Dreher; Justina A. V. Fischer (ETH Zurich, CER-ETH - Center of Economic Research, 2005)
This paper empirically analyzes the question whether government involvement in the economy is conducive or detrimental to life satisfaction in a cross-section of 74 countries. This provides a test of a longstanding dispute between standard neoclassical economic theory, which predicts that government plays an unambiguously positive role for individuals' quality of life, and public choice theory, that was developed to understand why governments often choose excessive involvement and regulation, thereby harming voters' quality of life. Our results show that life satisfaction decreases with higher government spending. This negative impact of the government is stronger in countries with a leftwing median voter. It is alleviated by government effectiveness – but only in countries where the state sector is already small.
Keywords: 330; Life satisfaction; Government; Regierung; Neue politische Ökonomie; Neoklassische Theorie; Schätzung; Zufriedenheit